Dietary Tomato Consumption and the Risk of Prostate Cancer: A Meta-Analysis - Luo, Jie; Ke, Dandan; He, Qingwei (Frontiers in Nutrition, 2021)
Objective: Several epidemiological studies have linked tomato products consumption with prostate cancer risk; however, the findings yielded inconsistent results. The aim of the present meta-analysis is to summary the evidence on this association based on eligible cohort studies. Materials and methods: A comprehensive literature search of articles was performed in March 2021 using PubMed, ISI Web of Science, and Scopus databases. A random-effects model was used to calculate the combined relative risks (RRs) and their corresponding 95% confidence intervals (CIs). Heterogeneity across studies was assessed using Cochran’s Q statistic and the I2 score Results: A total of 10 prospective studies were finally included in our meta-analysis. There was no evidence of a significant association between tomato products consumption and prostate cancer risk (RR 0.91, 95 % CI 0.79-1.03, P = 0.138). Subgroup meta-analyses were performed by tomato types, geographical region, publication year, study quality and number of cases. No significant associations were observed in any subgroups (all P > 0.05). No significant publication bias was observed using Begg’s test (P = 0.602) or Egger’s test (P = 0.957). Conclusion: The results of this meta-analysis indicated that tomato consumption was not related with the risk of prostate cancer. Further prospective large-scale cohort studies are still warranted to verify our findings.